2019
DOI: 10.1111/mec.15131
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐scale sampling suggests cryptic epigenetic structuring and insular divergence in Canada lynx

Abstract: Determining the molecular signatures of adaptive differentiation is a fundamental component of evolutionary biology. A key challenge is to identify such signatures in wild organisms, particularly between populations of highly mobile species that undergo substantial gene flow. The Canada lynx (Lynx canadensis) is one species where mainland populations appear largely undifferentiated at traditional genetic markers, despite inhabiting diverse environments and displaying phenotypic variation. Here, we used high‐th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 82 publications
1
44
0
Order By: Relevance
“…Patterns of low diversity and high differentiation were previously reported for NE Poland (Ratkiewicz et al, 2012(Ratkiewicz et al, , 2014Schmidt et al, 2009), as well as for Scandinavia and the Carpathians, using nuclear microsatellite markers and short mitochondrial sequences (Ratkiewicz et al, 2012(Ratkiewicz et al, , 2014 or an SNP set enriched for coding sequences (Förster et al, 2018). In contrast to westernmost populations, the current structure among Asian populations is shallow, similar to that found for Canadian lynx (F ST = 0.09-0.10; Meröndun, Murray, & Shafer, 2019), the overall pattern is compatible with an isolation by distance scenario ( Figure S14) and there is little support for more than one genetic cluster. Quite homogeneous genetic patterns across Asia are striking given the range of habitats occupied (e.g., from semidesert in Omnogovi, Mongolia, to boreal forest-tundra in Yakutia), and the several previously defined subspecies in this region.…”
Section: Holocenesupporting
confidence: 77%
See 1 more Smart Citation
“…Patterns of low diversity and high differentiation were previously reported for NE Poland (Ratkiewicz et al, 2012(Ratkiewicz et al, , 2014Schmidt et al, 2009), as well as for Scandinavia and the Carpathians, using nuclear microsatellite markers and short mitochondrial sequences (Ratkiewicz et al, 2012(Ratkiewicz et al, , 2014 or an SNP set enriched for coding sequences (Förster et al, 2018). In contrast to westernmost populations, the current structure among Asian populations is shallow, similar to that found for Canadian lynx (F ST = 0.09-0.10; Meröndun, Murray, & Shafer, 2019), the overall pattern is compatible with an isolation by distance scenario ( Figure S14) and there is little support for more than one genetic cluster. Quite homogeneous genetic patterns across Asia are striking given the range of habitats occupied (e.g., from semidesert in Omnogovi, Mongolia, to boreal forest-tundra in Yakutia), and the several previously defined subspecies in this region.…”
Section: Holocenesupporting
confidence: 77%
“…Even though we find little to no support for most of the subspecies discussed in the literature in recent years, the finding of shallow differentiation at neutral regions of the genome does not exclude the occurrence of locally divergent selection at particular genes (i.e., local adaptation). In addition, we cannot discard the possibility that the morphological variation that sustained previous subspecific delimitations represents plastic responses to local environments mediated by epigenetic changes, as suggested by a recent study of Lynx canadensis (Meröndun et al, 2019). Nevertheless, given our results, we argue that management plans should focus on reversing the demographic trends to prevent further genetic erosion in the most affected populations, and allowing natural evolutionary processes, including the facilitation of population connectivity through migratory corridors in human-altered habitats, as already postulated for lynx and other large carnivores in Europe (Boitani et al, 2015).…”
Section: Implications For Conservation Management and Taxonomymentioning
confidence: 92%
“…We showed that a modi ed epiGBS protocol originally proposed by Van Gurp et al [88] was applicable to further analyze patterns of cytosine methylation at a genome-wide scale in D. labrax. This is the rst use of epiGBS in sh and the second in an animal species (Canadian lynx [102]). The addition of a second restriction enzyme illustrates the exibility of the epiGBS and more generally of reduced-representation bisul te sequencing (RRBS) protocols to improve data acquisition and impact [103].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the lambda DNA genome was rebuilt as an extra reference for later calculation of the bisulfite conversion rate of each sample. The bulk methylation levels were analyzed for cytosine sites with ≥10X in each sample using CGmapTools [52]. A heatmap showing the average methylation levels of CG in bins across whole genomes (bin size, 500,000 bp) was generated by CGmapTools.…”
Section: Transcriptions Of Dna Methylationmentioning
confidence: 99%